Sheehy's manual of emergency care - Foley, Andi (Elsevier, 2024)
This book offers thorough coverage of the essentials emergency nurses need to know. Each condition commonly seen in the emergency setting is thoroughly addressed, from signs and symptoms, to diagnosis, treatment, developmental considerations, patient education, and more. -- Description from publisher's website.